2021
DOI: 10.3892/mmr.2021.12349
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B enhances apoptosis in gefitinib resistant non‑small cell lung cancer by modulating the miR‑17‑5p/STAT3 axis

Abstract: Tyrosine kinase inhibitors, such as gefitinib, are currently widely used as targeted therapeutics for non-small cell lung cancer (NSCLC). Although drug resistance has become a major obstacle to successful treatment, mechanisms underlying resistance to gefitinib remain unclear. Therefore, the present study aimed to investigate the impact of adjunctive cucurbitacin B (CuB) on gefitinib resistance (GR) in the PC9 cell line, including identifying underlying mechanisms. Reverse transcription-quantitative PCR demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Liu et al demonstrated that CuB regulated cell proliferation and apoptosis by suppressing the XIST/miR-let-7c/IL-6/STAT3 axis in NSCLC [ 132 ]. Similarly, Yu et al showed that CuB reduced the proliferation of gefitinib-resistant PC9 cells by modulating the miR-175p/STAT3 axis [ 133 ], while Yuan et al highlighted the inhibition of epithelial–mesenchymal transition (EMT) in TGF-β1 -induced A549 cells and gefitinib-resistant A549 cells via a decrease in ROS production and disruption of the PI3K/Akt/mTOR signaling pathway [ 134 ]. Furthermore, Liu et al found that CuB suppressed the growth and invasion of gefitinib-resistant NSCLC cells by inducing lysosomal EGFR degradation and by downregulating the CIP2A/PP2A/Akt signaling axis [ 135 ].…”
Section: Detailed Results and Discussionmentioning
confidence: 99%
“…Liu et al demonstrated that CuB regulated cell proliferation and apoptosis by suppressing the XIST/miR-let-7c/IL-6/STAT3 axis in NSCLC [ 132 ]. Similarly, Yu et al showed that CuB reduced the proliferation of gefitinib-resistant PC9 cells by modulating the miR-175p/STAT3 axis [ 133 ], while Yuan et al highlighted the inhibition of epithelial–mesenchymal transition (EMT) in TGF-β1 -induced A549 cells and gefitinib-resistant A549 cells via a decrease in ROS production and disruption of the PI3K/Akt/mTOR signaling pathway [ 134 ]. Furthermore, Liu et al found that CuB suppressed the growth and invasion of gefitinib-resistant NSCLC cells by inducing lysosomal EGFR degradation and by downregulating the CIP2A/PP2A/Akt signaling axis [ 135 ].…”
Section: Detailed Results and Discussionmentioning
confidence: 99%
“…Natural products ( 116 Furthermore, sucurbitacin B inhibits proliferation and triggers apoptosis of gefitinib-resistant lung cancer cells by upregulating miR-17-5p. 117 Resveratrol suppresses LPS-triggered injury in keratinocytes by upregulating miR-17-5p. 118 In contrast, miR-17-5p is downregulated by retinoic acid in acute myeloid leukemia cells, 119 promoting the neuronal differentiation of neuroblastoma cells (Table 4).…”
Section: Mir-17-5pmentioning
confidence: 99%
“…Celastrol suppresses vascular endothelial growth factor (VEGF)‐promoted proliferation and migration, and inhibits hypoxia‐triggered angiogenesis in HRMEC cells by upregulating miR‐17‐5p 116 . Furthermore, sucurbitacin B inhibits proliferation and triggers apoptosis of gefitinib‐resistant lung cancer cells by upregulating miR‐17‐5p 117 . Resveratrol suppresses LPS‐triggered injury in keratinocytes by upregulating miR‐17‐5p 118 .…”
Section: Connections Of Pp2a‐modulating Mirnas To Pp2a‐modulating Nat...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the semisynthetic derivative of CuB, DACE (2-deoxy-2-amine-cucurbitacin E), and paclitaxel (PTX) showed potential in vitro synergistic antiproliferative effects in A549 cells [ 99 ]. In addition, CuB can reduce the proliferation of gefitinib-resistant (GR) PC9 cell lines by regulating the miR-17-5p/STAT3 axis [ 100 ].…”
Section: Combination Medication and Multichannel Antitumormentioning
confidence: 99%